Teknik Analisa Fundamental Dalam Mempengaruhi Return Saham Dengan Harga Saham Sebagai Variabel Moderating - Adi Mila Nur Affiffa; Andi Kartika (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The capital market is an important instrument in the development of the world economy. Every year the capital market develops very rapidly with evidence of an increase in the number of outstanding shares and a high volume of stock trading. This study aims to analyze fundamentals that affect stock returns including CR, DER and ROA and to test whether stock prices are able to moderate the relationship between these variables. This research was conducted on food and beverages companies listed on the Indonesia Stock Exchange from 2016 to 2020. The data used is the financial report (annual report). The sampling method used purposive sampling method. Test to see the effect using multiple linear regression analysis. The results showed that CR had a significant negative effect on stock returns. DER has a significant positive effect on stock returns. ROA has a significant negative effect on stock returns. Stock prices are able to moderate the relationship of CR, DER and ROA to stock returns with a weakening function. The coefficient of determination test shows that CR, DER and ROA are able to provide an overview of changes in stock prices of 63.9% and the remaining 36.1% is influenced by other variables outside the study. Keywords : current ratio, debt to equity ratio, return on assets, stock return, stock price